Taxonomy and phylogeny of entomopathogenic fungi from China—revealing two new genera and thirteen new species within Clavicipitaceae (Hypocreales, Ascomycota) - Zhi-Qin Wang; Zhi-Li Yang; Jing Zhao; Jin-Mei Ma; De-Xiang Tang; Zong-Li Liang; Jian-Hong Li; Xin-Mao Zhou; Hong Yu (MycoKeys)
Scale insects (Coccidae, Hemiptera) and whiteflies (Aleyrodidae, Homoptera) are diminutive, ubiquitous, sap-sucking plant parasites, many of which are serious agricultural pests. Over the course of several years, an investigation into entomopathogenic fungi affecting scale insects and whiteflies resulted in the collection of 13 novel species of Clavicipitaceae in Yunnan and Hainan Provinces, China. Based on three-loci (nrLSU, tef-1a, and rpb1) phylogenetic analysis and morphological evidence, it was determined that two new genera, Paramoelleriella and Polymicrospora, each encompassed a new species. Additionally, two new species of Hypocrella s. str. and nine new species of Moelleriella were identified. Within the Moelleriella clade, seven new species were assigned to the Effuse clade and two to the Globose clade. Hypocrella s. str. and Samuelsia were included in the Pulvinate clade, to which the new genus Paramoelleriella is closely related, although it forms a distinct branch. Paramoelleriella species exhibited characteristics similar to those of Moelleriella, including globose to subglobose, yellow to orange teleomorphic stromata, with perithecia densely arranged and fully embedded in the stromatal tissue. Its ascospores disarticulated into short-cylindrical part-spores, and the conidiomata featured large, widely open orifices bearing fusoid conidia curved to one side. Species of the new genus Polymicrospora were characterized by thin-pulvinate, snow-white to off-white teleomorphic stromata with surface smooth. These species possessed numerous obpyriform or oval, semi-embedded, and densely arranged perithecia, cylindrical asci, and ascospores that disarticulated into small, oval part-spores in large quantities. This study introduces two new genera and 13 new species, accompanied by detailed illustrations and descriptions.